Get Smart: Learning and partnership with Ethiopia’s Health Extension Programme to re-envision contraceptive service delivery to young couples [version 1; peer review: 2 approved] - Gabrielle Appleford; Claire Cole; Metsehate Ayenekulu; Sue Newport; Emma Mulhern (Gates Open Research, 2019)
Background: Adolescents 360 (A360) implements the Smart Start (SS) programme through Ethiopia’s Health Extension Programme (HEP). SS is premised on financial planning as an entry point to discuss family planning (FP) with newly married couples and central to its delivery are the health extension workers (HEW). This article evaluates the A360 experience and learning from the process evaluation implemented by Itad to understand contextual barriers and enablers from the perspective of the HEW. Methods: A purposive sampling strategy was employed whereby 27 key stakeholders were identified from Oromia, Addis Ababa and Amhara, based on exposure to the SS programme. Findings from the action research were shared with A360 through a one day sounding workshop. Results: Findings revealed that many local government and communal respondents do not view adolescent pregnancy as a problem, unless out of wedlock, and adolescent pregnancy is closely linked to early marriage. As a result, some providers, including HEWs, acknowledged that married adolescent girls were previously ‘neglected’ by them, while husbands indicated that they had not previously been included in FP counselling. Findings also revealed some challenges with SS implementation as HEWs were ‘deprioritizing’ the intervention and many HEWs had been in situ for several years and were overworked and frustrated. Against this backdrop, A360 was viewed as adding to the HEW workload. While the programme design was focused on adolescent users, there was increasing recognition that HEWs also needed to be at the centre of solution design. Conclusions: Despite challenges associated with the HEP, Ethiopia FP2020 plans to support the ‘next generation’ of HEWs, including a focus on adolescents and youth. To gain deeper insight and put the HEW at the centre of design, A360 will continue to work with the process evaluation to understand contextual barriers and enablers from the perspective of the HEW.